Franz Kafka & Narrativa-carrasco: investigações sobre morte, experimentação e afirmação - Raphaelli, Matheus Bagaiolo (2022)
The article develops the concept of “hangman-narrative” in order to explain an important dynamic of the Kafkian narrative: its particular development through selfdestruction, i.e., a series of beginnings without their corresponding closures and without any possibility of transcendence. To do so, the article will start from the idea of absurdity and will analyze some of the Czech author’s writing procedures that explain such mechanism, more specifically in his short stories. One of the fundamental traits of this hangman-narrative examined is how it constitutes itself as a way out of western nihilism. For this purpose, the philosophy of Nietzsche and Deleuze are put into dialogue in order to reach, at the end, the relationship between literary experimentation and the concept of immanence proposed by Kafka